Revolutionizing Cargo Transport: The Impact of Innovative Technologies - Amel Kosovac; Adisa Medic\'; Irfan Córic\'; Sabina Hadrovic\' (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2023)
For many years, cargo traffic was marred by inefficiency, slow work systems, extensive paperwork and inaccuracies in the supply chain and transportation to the final destination. Processes within the chain itself entailed slow work, which resulted in large deviations in terms of transport and delivery time to the end user. To overcome these shortcomings and improve cargo traffic, the focus of the work will be on the application of innovative technologies in cargo traffic, the analysis of the application and the advantages it provides. A special aspect of the work is the analysis of cargo traffic in Bosnia and Herzegovina and the application of innovative technologies in its area.
Keywords: L91; L93; L96; 330; innovative technologies; cargo; logistics; air traffic